Penguatan Literasi Finansial Melalui Gemar Menabung Siswa Sekolah Dasar - Dri Puspita, Wulan; Safrilia, Adisti; Saputri, Ananda Herta (Lembaga Dongan Dosen, 2023)
Financial literacy is the ability to manage finances. The Financial Services Authority (OJK) has advocated for financial literacy programs in schools to encourage children to develop a habit of saving and create a lasting impact. Money is a tool that can be both a solution and a problem if not managed properly. Students at Duwet Elementary School are generally aware of the functions of money but struggle to grasp its true meaning. Their inability to distinguish between needs and wants leads to their pocket money being spent quickly every time it's given. This doesn't mean that spending money on treats is prohibited, but it's more appropriate to allocate funds for desires, necessities, and savings after carefully considering their usage. This knowledge is lacking among Duwet Elementary School students. The challenge of managing money becomes a reason for our outreach team to provide financial literacy training through promoting a love for saving. Early childhood is a phase when memories are easily retained. Hence, activities are conducted to foster financial literacy. The outcomes of these activities demonstrate the children's enthusiasm in participating in the program and their understanding of the purpose of saving.